2017
DOI: 10.22456/2527-2616.75607
|View full text |Cite
|
Sign up to set email alerts
|

Stability-Indicating Method for Determination of Tizanidine Hydrochloride in Pharmaceutical Lc-Cad Method Using Chemometric Approach

Abstract: A new LC method for tizanidine hydrochloride in tablet dosage form using a charged aerosol detector (CAD) is described. The influence of various parameters on chromatographic system was investigated by factorial designs and Derringer's desirability. Chromatographic conditions were: mobile phase constituted of acetonitrile and ammonium acetate buffer 17 mM (60:40; v/v), column oven at 39 °C and flow rate 0.8 mL.min-1 performed in on Acclaim Trinity P1 column UV at 230 nm. Thus, it was possible to validate a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Literature reveals, several analytical methodologies used for the estimation of Tizanidine, either as a single entity or as combined entity with another drug. These methods include spectrophotometric and HPLC methods (Brandalise et al, 2017;Devarajan and Sivasubramanian, 2006;Mantri et al, 2005;Ramaa et al, 2006;Reddy et al, 2008;Samel and Raman, 2009;Subramanian et al, 2004;Vijayakumar et al, 2010). Recent findings have revealed that even significantly low levels of impurities affect the safety as well as the efficacy of a drug product.…”
Section: Introductionmentioning
confidence: 99%
“…Literature reveals, several analytical methodologies used for the estimation of Tizanidine, either as a single entity or as combined entity with another drug. These methods include spectrophotometric and HPLC methods (Brandalise et al, 2017;Devarajan and Sivasubramanian, 2006;Mantri et al, 2005;Ramaa et al, 2006;Reddy et al, 2008;Samel and Raman, 2009;Subramanian et al, 2004;Vijayakumar et al, 2010). Recent findings have revealed that even significantly low levels of impurities affect the safety as well as the efficacy of a drug product.…”
Section: Introductionmentioning
confidence: 99%